2022
DOI: 10.1002/adfm.202211124
|View full text |Cite
|
Sign up to set email alerts
|

Defect‐Rich Hierarchical Porous Mn‐Doped CoP Hollow Microspheres Accelerate Polysulfide Conversion

Abstract: Lithium-sulfur batteries (LSBs) with high theoretical specific capacities have been regarded as the development direction of next generation energy storage. However, the shuttle effect of lithium polysulfides (LiPSs) and the retardation of conversion kinetics have hindered their industrial application. Herein, Mn selectively doped CoP hollow microspheres are designed and synthesized to trap LiPSs and enhance Li-S reaction kinetics. Mn is successfully doped into (100) surfaces of Co 3 O 4 via simple hydrotherma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 66 publications
(110 reference statements)
0
19
0
Order By: Relevance
“…Self-discharge is a significant challenge faced by many high-rate energy storage devices. While self-discharge is slow and therefore less discussed for lithium-ion batteries (4% per month), it has been identified in nickel–cadmium batteries (20% per month) and nickel–metal hydride batteries (25% per month). It is worth noting that the self-discharge rate of supercapacitors reaches 1.8% per day, which severely limits its application. , Current understanding has attributed the mechanisms of self-discharge for supercapacitors to three processes: Faradaic reactions, charge redistribution, and Ohmic leakage. , The Faradaic reactions are caused by the presence of impurities in the electrolyte that are capable of redox reactions. , Charge redistribution refers to the transfer loss of absorbed charged ions due to the concentration gradient .…”
mentioning
confidence: 99%
“…Self-discharge is a significant challenge faced by many high-rate energy storage devices. While self-discharge is slow and therefore less discussed for lithium-ion batteries (4% per month), it has been identified in nickel–cadmium batteries (20% per month) and nickel–metal hydride batteries (25% per month). It is worth noting that the self-discharge rate of supercapacitors reaches 1.8% per day, which severely limits its application. , Current understanding has attributed the mechanisms of self-discharge for supercapacitors to three processes: Faradaic reactions, charge redistribution, and Ohmic leakage. , The Faradaic reactions are caused by the presence of impurities in the electrolyte that are capable of redox reactions. , Charge redistribution refers to the transfer loss of absorbed charged ions due to the concentration gradient .…”
mentioning
confidence: 99%
“…Figure d shows the high-resolution fine spectrum of Mn 2p. The peaks at binding energies of 640 and 645 eV corresponded with the 2p 2/3 peaks of Mn 2+ and Mn 3+ , respectively, and the 2p 2/1 peaks corresponded with 654 and 656 eV, respectively Figure e shows deconvoluted peaks at 709, 722 and 711, 725 eV, which corresponded with Fe 2+ and Fe 3+ ions, respectively .…”
Section: Results and Discussionmentioning
confidence: 95%
“…Compared with the peak of manganese in the 3DCS-MO@C material after adsorption, the peak of the 3DCS-FMO@C material shifted to the direction of low binding energy after Li 2 S 6 adsorption. Thus, 3DCSS-FMO@C had a stronger charge transfer after adsorption and charge transfer from Li 2 S 6 to Mn . The S 2p fine spectrum in Figure c revealed that the terminal sulfur (ST-1) and bridge sulfur (SB0) corresponded with the binding energy positions of 161.1 and 162.7 eV, respectively, and the peak of the 3DCS-FMO@C material moved to the high field after adsorption, indicating that S had undergone a reduction reaction and lost electrons.…”
Section: Results and Discussionmentioning
confidence: 96%
See 2 more Smart Citations